(3QSGdI aj LhGR GdEbJOGA HGdeNGda hYOegs - (3GHf CHj TQjas
(3ChdgG (B:s
(3bGd UGMH GdJJQNGfjI ceGd GdOjf Hf GdgeGe ai LhGR GdUdGI hYOeg dQCi GdebJOi ai Mb faSg dG dQCi CeGeg adh Yde GdebJOi ef GdEeGe eG jaSO GdUdGI s
(3BNQgG (B:s
(3CLjH HCf eNGdaI GdeNGda ai GdePgH djS HecQhg adG jUdi dEMJeGd GdaSGO Ch GdcQGgg hGddg JYGdi CYde hCMce HGdUhGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B7s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3eUOQ GbJfGA GdCUd (B:s
(3GdeOQSI GdCMeOjI (B_ (3GdehUd (B(115) s
Keywords: (3GdeLGejYs